Spatial Distribution of Adults of Triozoida limbata (Enderlein) (Hemiptera: Triozidae) in Guava Plants - Marcelino, M. C.S.; Barbosa, J. C. [UNESP] (Springer Nature, 2016)
The psyllid Triozoida limbata (Enderlein) (Hemiptera: Triozidae) is a major pest in guava, feeding primarily on new shoots. Despite its importance, there are no studies on the spatial distribution of T. limbata on guava. Such studies are needed to establish sequential sampling plans for decision making in pest control. Thus, an experiment was carried out in a 9-year-old commercial guava orchard divided into 100 sampling units or plots. Double-sided yellow sticky traps were placed on one plant per plot (sample unit) to capture and monitor T. limbata adults from April 2011 to May 2012. To determine the insect distribution in the area, we calculated the variance-to-mean ratio index (I), the Morisita index (Iδ), Green’s coefficient (Cx), and the k exponent of the negative binomial distribution. Most of the samples showed that the adults had a moderate to highly aggregated distribution. Statistical models were also used to study the pest spatial distribution by fitting the number of adults captured to the Poisson and negative binomial distributions. The negative binomial distribution model best fitted the data of the number of adult psyllids captured by the traps, which is consistent with an aggregated distribution.
Keywords: Dispersion indices; negative binomial distribution; Psidium guajava; psyllid